The Threat to the German Welfare State - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2000)
Germany is in a dilemma. Low wage competition via product and factor markets increases the demands on the welfare state, but increased systems competition in the context of international factor mobility reduces the possibilities of maintaining it. The welfare state has important allocative functions. It is an insurance against career risks and it stimulates risk taking and economic growth. However, it also has severe moral hazard effects by reducing work incentives. To help the welfare state survive and improve its performance, the paper advocates the home country principle for the treatment of immigrants, the introduction of funded elements in the pension system, and employment subsidies at the expense of ordinary welfare payments.
Keywords: 330